4D Blood Flow Reconstruction Over the Entire Ventricle From Wall Motion and Blood Velocity Derived From Ultrasound Data - Gomez,A; de,Vecchi A; Jantsch,M; Shi,W; Pushparajah,K; Simpson,JM; Smith,NP; Rueckert,D; Schaeffter,T; Penney,GP (IEEE Transactions on Medical Imaging, 2015)
We demonstrate a new method to recover 4D bloodflow over the entire ventricle from partial blood velocity measurementsusing multiple colour Doppler images and ventricularwall motion estimated using BMode images. We applyour approach to realistic simulated data to ascertain the ability ofthe method to deal with incomplete data, as typically happens inclinical practice. Experiments using synthetic data show that theuse of wall motion improves velocity reconstruction, shows moreaccurate flow patterns and improves mean accuracy particularlywhen coverage of the ventricle is poor. The method was appliedto patient data from 6 congenital cases, producing results consistentwith the simulations. The use of wall motion produced moreplausible flow patterns and reduced the reconstruction error in allpatients.